Voice of an Elder: Zhaawonde - Dawn of a New Day - Shawanda, Gordon; Wesley-Esquimaux, Cynthia (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2010)
This paper evolved, maybe ‘was birthed’ is an even better term given the circumstances, out of an engagement process that brought Gordon Shawanda and several university students together over an academic year. Gordon was invited to attend my Aboriginal Spirituality class at the University of Toronto in September 2009. He liked being there so much that he came each week, sitting through lectures, reading the materials, and participating with unerring grace in the many discussions over the entire year. We were all touched by his presence, his quiet dignity, and his deep interest in our academic learning and sharing experience. Gordon embodies what modern education is trying to get right, the bringing together of theory and practice, and the unveiling of the kind of humanity that can bring Indigenous Knowledge alive for all young people everywhere. Gordon was inspired by their enthusiastic receiving of his words to write down his story. This paper is his first real attempt to express the pain and healing he has experienced over his adulthood. I am honoured and humbled to (gently) edit this work for publication. This is a story that comes directly from the heart and soul of one man, but is the lived experience of many of our people who attended Indian Residential Schools in Canada. It is organized into four parts.